Christian translations of the Qur'an into Yoruba and their historical background - Solihu, Abdul Kabir Hussain; Abdulhameed, Abdulganiy Akorede (Routledge, 2015)
This study considers the emergence of the Christian-led Yoruba translations of the Qur'an in south-western Nigeria. The proliferation of translations of religious texts played a significant role in Christian engagement with Islam in Africa in the nineteenth century. With their contact with the European Christians in Sierra Leone following the abolition of the transatlantic slave trade, a sizable number of Yoruba recaptives returned to Yorubaland as missionaries and embarked on translating religious texts into the Yoruba language as part of Christian mission. In 1906, the Reverend M. S. Cole published the first Yoruba translation of the Qur'an, which was also the first translation into an African language. In 1965, E. K. Akinlade published the second Yoruba translation of the Qur'an. This article relates the Christian-led Yoruba translations to a larger scheme of the Christian missionary engagement with Islam and the Yoruba Muslims on a scriptural basis, which was inaugurated by Bishop Crowther in the second half of the nineteenth century. It examines the theological bases and historical circumstances that led to the publication of the early Yoruba translation of the Qur'an. The article then provides an overview of the works in an attempt to identify their aid materials and the motives for the translations.